2020
DOI: 10.1186/s13287-020-01940-z
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA H19 regulates the therapeutic efficacy of mesenchymal stem cells in rats with severe acute pancreatitis by sponging miR-138-5p and miR-141-3p

Abstract: Background Patients with severe acute pancreatitis (SAP), which is characterized by high morbidity and mortality, account for an increasing medical burden worldwide. We previously found that mesenchymal stem cells (MSCs) could attenuate SAP and that expression of long noncoding RNA H19 (LncRNA H19) was upregulated in rats receiving MSCs. In the present study, we investigated the mechanisms of LncRNA H19 regulating the therapeutic efficacy of MSCs in the alleviation of SAP. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Li et al demonstrated that miR-141-3p is important for osteogenic differentiation of stem cells from the apical papillae (SCAPs) [ 28 ]; miR-141-3p inhibits the proliferation of SCAPs and accelerates cellular senescence by downregulating the expression of YAP [ 28 ]. Recently, it has been found that knockdown of miR-141-3p can promote the proliferation level of mesenchymal stem cells by upregulating the expression of β -catenin, C-Myc, and cyclin D1 [ 29 ]. Despite these findings, the effect of miR-141-3p on the osteogenic differentiation ability of hPDLSCs under an inflammatory microenvironment has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al demonstrated that miR-141-3p is important for osteogenic differentiation of stem cells from the apical papillae (SCAPs) [ 28 ]; miR-141-3p inhibits the proliferation of SCAPs and accelerates cellular senescence by downregulating the expression of YAP [ 28 ]. Recently, it has been found that knockdown of miR-141-3p can promote the proliferation level of mesenchymal stem cells by upregulating the expression of β -catenin, C-Myc, and cyclin D1 [ 29 ]. Despite these findings, the effect of miR-141-3p on the osteogenic differentiation ability of hPDLSCs under an inflammatory microenvironment has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are involved in the progression of AP (1,42). The current study demonstrated that TUG1 expression was upregulated in AR42J cells cotreated with caerulein and LPS, suggesting that TUG1 may act as a promoter of AP.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is a type of inflammatory disease, which results from the dysregulation of pancreatic enzymes in the pancreas (1,2). AP is very common, has a considerably high mortality rate and can cause systemic complications (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, no data have been presented to verify the effect of NAFLD-derived lncRNA MALAT1 on the regulation of AP. It is reported that lncRNAs are involved in the progression of acute pancreatitis [ 15 , 16 ], but the influence of NAFLD-derived MALAT1 in acute pancreatitis remains blurry.…”
Section: Introductionmentioning
confidence: 99%